2014
DOI: 10.1089/tmj.2013.0162
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assessment Tool of Disease Activity of Rheumatoid Arthritis by Using a Smartphone Application

Abstract: The results suggest that noninvasive self-assessment of a combination of joint symptoms, limitations of daily activities, and walking ability can adequately predict disease activity of RA with a smartphone application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 31 publications
(35 reference statements)
0
25
0
1
Order By: Relevance
“…Compared to our study, 3 previous remote disease activity assessment studies have used different, significantly more complex approaches. A cross‐sectional study by Nishiguchi et al of 65 patients demonstrated that a smartphone application can be used for measuring RA disease activity . In this study, patients gave a disease activity assessment using the modified HAQ, self‐assessed tender and swollen joint counts, and self‐measured their gait using an accelerometer.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to our study, 3 previous remote disease activity assessment studies have used different, significantly more complex approaches. A cross‐sectional study by Nishiguchi et al of 65 patients demonstrated that a smartphone application can be used for measuring RA disease activity . In this study, patients gave a disease activity assessment using the modified HAQ, self‐assessed tender and swollen joint counts, and self‐measured their gait using an accelerometer.…”
Section: Discussionmentioning
confidence: 99%
“…Only apps available in New Zealand app stores and in English language were included. An app for patient-led monitoring of RA disease activity has been developed in Japanese, which includes ACR and EULAR recommended instruments and diseases activity measures [12]. However, a preliminary search of the iTunes stores of 4 other English-speaking countries with the term “rheumatoid arthritis” suggested that the search of the New Zealand app stores has captured all relevant apps in the English language.…”
Section: Discussionmentioning
confidence: 99%
“…Younger age, current smartphone ownership, and use of email, Internet, and short messaging services were all associated with willingness to use apps for RA self-management. A small Japanese study reported that patient self-reported disease activity data using validated instruments correlated well with rheumatologist-assessed RA disease activity [12]. Furthermore, there is some evidence that mHealth interventions such as smartphone apps may improve outcomes for people with other chronic diseases [7,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The smartphones are widely popular devices, and the rapidity of app development is a fertile soil for developing many low-cost systems providing a lot of data about daily life activities of subjects (for example, many apps assessing running performance are already available for joggers). Recent studies showed a degree of accuracy using smartphone with a gait analysis app comparable to that of a conventional tri-axial accelerometer specifically developed for gait assessment (ICC ranging between 0.75 to 0.90, validity p<0.01) [160,161].…”
Section: Five Year Perspective Viewmentioning
confidence: 99%